Waste Management in Bengkulu Between Hope and Reality - Sari, Yenny Puspita; Adriadi, Rekho; Darmi, Titi; Rosidin, Rosidin (Jurnal Multidisiplin Dehasen (MUDE), 2025)
The purpose of this study is to evaluate the waste management policy in Bengkulu City. The Bengkulu City Government introduced community-based waste management through the Community Empowerment Unit (LPM) at the end of 2022. Observations show that only 48% of the waste in Bengkulu is successfully removed every day. This figure highlights the serious challenges facing waste management in Bengkulu. There may be several reasons for the low waste removal rate, such as: B. Limited capacity of the landfill site (TPA) and lack of a waste transportation fleet. This study adopts a descriptive approach combined with a qualitative approach to describe the existing conditions. This study uses a qualitative approach to conduct a descriptive study, which aims to reveal facts to evaluate the waste management policy in Bengkulu. There are still some obstacles and problems in the implementation process. Waste management at the Kelurahan level continues to face problems, including continued littering by some people. Existing efforts are not necessarily sufficient to achieve truly effective waste management policy objectives. This suggests that there are gaps in access to information, lack of motivation, low participation, and insufficient public awareness due to various factors. The implementation of waste management policy in Bengkulu City is not ideal. Effectiveness and efficiency are low. Resources are limited. The adequacy of services is not fully guaranteed. Justice is not evenly distributed between different areas. The government's responsiveness is weak and the policy does not meet the needs of the people. The policy is conceptually on a good track for improvement, but further improvement is needed, and it has a clear impact on environmental quality and public behavior.